2019
DOI: 10.1091/mbc.e19-08-0469
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage triggers increased mobility of chromosomes in G1-phase cells

Abstract: During S phase in Saccharomyces cerevisiae, chromosomal loci become mobile in response to DNA double-strand breaks both at the break site (local mobility) and throughout the nucleus (global mobility). Increased nuclear exploration is regulated by the recombination machinery and the DNA damage checkpoint and is likely an important aspect of homology search. While mobility in response to DNA damage has been studied extensively in S phase, the response in interphase has not, and the question of whether homologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Where long genes are also poor in initiation sites, delayed replication in concert with the extended distance of fork travel renders these sites vulnerable to instability ( 78 ). Multiple unresolved lesions within long genes promotes clustering—particularly in G1 cell cycle phase when chromatin has higher mobility ( 80 ) and HDR repair of coding sequence is restricted ( 81 ). Amente et al.…”
Section: Discussionmentioning
confidence: 99%
“…Where long genes are also poor in initiation sites, delayed replication in concert with the extended distance of fork travel renders these sites vulnerable to instability ( 78 ). Multiple unresolved lesions within long genes promotes clustering—particularly in G1 cell cycle phase when chromatin has higher mobility ( 80 ) and HDR repair of coding sequence is restricted ( 81 ). Amente et al.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also identified a Mec1-dependent phosphorylation of the kinetocore protein Cep3 as an essential player in global chromatin mobilization (Strecker et al, 2016). In addition to checkpoint kinases, Rad51 and Rad52 HR proteins are required to facilitate global chromatin dynamics (Seeber et al, 2013;Miné-Hattab et al, 2017;Smith et al, 2018Smith et al, , 2019. Further, studies in yeast and mammalian cells suggest that cytoplasmic actin and microtubules induce a global chromatin "shake-up" in response to DSB formation (Lottersberger et al, 2015;Spichal et al, 2016;Amitai et al, 2017;Lawrimore et al, 2017).…”
Section: Msd Analyses Reveal Increased Nuclear Exploration Of Damaged and Undamaged Chromatin In Response To Dsbsmentioning
confidence: 98%
“…This change in chromatin mobility in response to DNA damage likely reflects the exploration of the nuclear space during "homology search" (Kalocsay et al, 2009;Dion et al, 2012;Miné-Hattab and Rothstein, 2012;Neumann et al, 2012;Agmon et al, 2013;Cho et al, 2014;Saad et al, 2014;Herbert et al, 2017;Miné-Hattab et al, 2017), i.e., the process where a resected DSB covered by a Rad51 nucleoprotein filament scans the genome in search of a homologous donor. Second, undamaged chromatin also becomes more dynamic during DSB repair, albeit to a lesser extent than repair sites (Figure 1B) (Chiolo et al, 2011;Krawczyk et al, 2012;Miné-Hattab and Rothstein, 2012;Seeber et al, 2013;Lottersberger et al, 2015;Strecker et al, 2016;Herbert et al, 2017;Lawrimore et al, 2017;Miné-Hattab et al, 2017;Caridi et al, 2018a;Smith et al, 2019;Zada et al, 2019). The significance of the genome-wide increase in nuclear exploration is still under debate, but this response might increase the frequency of DNA contacts to facilitate homology search (Gehen et al, 2011;Neumann et al, 2012;Mine-Hattab and Rothstein, 2013;Amitai and Holcman, 2018), or reflect chromatin relaxation to promote access for repair (Kruhlak et al, 2006;Ziv et al, 2006;Seeber et al, 2013;Delabaere and Chiolo, 2016).…”
Section: Introduction: Chromatin Explores a Larger Nuclear Volume In Response To Dna Damagementioning
confidence: 99%
“…These studies also identified a Mec1-dependent phosphorylation of the kinetocore protein Cep3 as an essential player in global chromatin mobilization ( Strecker et al, 2016 ). In addition to checkpoint kinases, Rad51 and Rad52 HR proteins are required to facilitate global chromatin dynamics ( Seeber et al, 2013 ; Miné-Hattab et al, 2017 ; Smith et al, 2018 , 2019 ). Further, studies in yeast and mammalian cells suggest that cytoplasmic actin and microtubules induce a global chromatin “shake-up” in response to DSB formation ( Lottersberger et al, 2015 ; Spichal et al, 2016 ; Amitai et al, 2017 ; Lawrimore et al, 2017 ).…”
Section: Msd Analyses Reveal Increased Nuclear Exploration Of Damagedmentioning
confidence: 99%
“…This change in chromatin mobility in response to DNA damage likely reflects the exploration of the nuclear space during “homology search” ( Kalocsay et al, 2009 ; Dion et al, 2012 ; Miné-Hattab and Rothstein, 2012 ; Neumann et al, 2012 ; Agmon et al, 2013 ; Cho et al, 2014 ; Saad et al, 2014 ; Herbert et al, 2017 ; Miné-Hattab et al, 2017 ), i.e., the process where a resected DSB covered by a Rad51 nucleoprotein filament scans the genome in search of a homologous donor. Second, undamaged chromatin also becomes more dynamic during DSB repair, albeit to a lesser extent than repair sites ( Figure 1B ) ( Chiolo et al, 2011 ; Krawczyk et al, 2012 ; Miné-Hattab and Rothstein, 2012 ; Seeber et al, 2013 ; Lottersberger et al, 2015 ; Strecker et al, 2016 ; Herbert et al, 2017 ; Lawrimore et al, 2017 ; Miné-Hattab et al, 2017 ; Caridi et al, 2018a ; Smith et al, 2019 ; Zada et al, 2019 ). The significance of the genome-wide increase in nuclear exploration is still under debate, but this response might increase the frequency of DNA contacts to facilitate homology search ( Gehen et al, 2011 ; Neumann et al, 2012 ; Mine-Hattab and Rothstein, 2013 ; Amitai and Holcman, 2018 ), or reflect chromatin relaxation to promote access for repair ( Kruhlak et al, 2006 ; Ziv et al, 2006 ; Seeber et al, 2013 ; Delabaere and Chiolo, 2016 ).…”
Section: Introduction: Chromatin Explores a Larger Nuclear Volume In mentioning
confidence: 99%